Analysis of the Role of Information Technology Management in Improving Public Services in Sesumpu Village - Agusman, Agusman; Suyuthi, Nurmadhani Fitri; Mujahid, Mujahid (Newinera Publisher, 2024)
This study aims to analyze the role of information technology management in improving public services in Sesumpu Village. With a qualitative approach, data were collected through interviews, observations, and document analysis. The results of the study indicate that the application of information technology has accelerated the administrative process, increased communication efficiency, and strengthened coordination between village officials. Supporting factors include government support, enthusiasm of village officials, and community participation. However, obstacles such as limited human resources, inadequate infrastructure, and low digital literacy are still major challenges. The recommended strategies include developing online service applications, increasing internet network capacity, continuous staff training, and educating the community to improve the use of technology. These findings demonstrate the importance of a strategic and inclusive approach to information technology management in order to create more efficient and transparent public services.